STRATEGIC ASPECTS OF THE PRODUCTION AND ECONOMIC POTENTIAL OF URBAN INVESTMENT AND CONSTRUCTION SECTOR - Bredikhina, Natalia Vladimirovna (Journal of Applied Engineering Science, 2021)
The formation of the production and economic policy of enterprises of the urban investment and construction sector presupposes determination of objectives and development strategies for the short and long terms, based on the potential capabilities of each enterprise and its provision with appropriate resources.The article presents the organizational and managerial analysis of the overall assessment of the enterprise potential and functional areas to identify enterprise’s strategical strengths and weaknesses. The analysis of such components as the intensity of construction (reconstruction), labour productivity, technology and management of construction production, urban planning value of the renovated (built-up) area, corporate relations as well as the competitiveness of the company’s construction products.
Keywords: urban investment and construction sector, business reliability, construction company, enterprise strategy, production and economic potential.